Transformasi Sistem Pendidikan Islam Pada Masa Pendudukan Jepang di Indonesia (1942-1945) - Andi Reski Amelia; Fathir Qadri Syam; Idrus L (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the transformation of Islamic education systems in Indonesia during the Japanese occupation (1942–1945) through a historical-critical qualitative approach based on primary and secondary literature sources. The analysis explores institutional restructuring, curricular recontextualization, and the socio-cultural dynamics shaping educational practices under military rule. Findings indicate that Japanese policies imposed administrative control and ideological alignment, leading to structural adjustments within Islamic educational institutions. Simultaneously, curriculum simplification and pedagogical adaptations emerged as strategic responses to maintain the continuity of Islamic knowledge within constrained environments. The study also highlights the pivotal role of local actors, including ulama, santri, and Islamic organizations, in mediating between colonial authority and community needs. Their adaptive strategies fostered resilience, preserved religious identity, and facilitated the transmission of knowledge through flexible social networks. The interaction between external pressure and internal agency generated a dynamic transformation that extended beyond survival, contributing to the formation of a national Islamic education identity. This transitional phase significantly influenced the post-independence integration of Islamic education into the broader national education system.